Leveling and gravity surveys at Syowa Station, Antarctica - Katsutada Kaminuma; Kaoru Abe; Hitoshi Tanaka (National Institute of Polar Research, 1984)
Leveling routes for detecting the ground tilt caused probably by the regional deglaciation were established by the 20th and 23rd Japanese Antarctic Research Expedition (JARE-20 and -23) in East Ongul Island, Antarctica. The leveling surveys were carried out according to the first order leveling survey method of Geographical Survey Institute in Japan during the winter seasons of 1979 and 1982. The accuracy of the surveys between the leveling points was better than ±0.4mm. Gravity surveys using LaCoste-Romberg gravimeter model G were also carried out in 1979 and 1982. Twenty-five gravity stations were established in West Ongul Island in 1979. The gravity at six stations out of twenty-five was also measured by JARE-19 and -22 in 1978 and/or 1981. The gravity values of the two or three independent surveys at the same station were consistent with each other within the accuracy of 0.1 mgal. Five gravity stations were also established at the geodetic control points in small islands off Langhovde, and three stations near the water tube tiltmeter of two components at Syowa Station.